Application of Autogenous Dermis Combined With Local Flap Transplantation in Repair of Titanium Mesh Exposure After Cranioplasty. Issue 2 (15th March 2023) - Wei, Zhiyi; Yang, Xiaolan; Lin, Tianlai; Zhu, Jingfa; Fang, Xiangjian; Zhu, Yixin; Cheng, Juntao
Abstract : Objectives: To investigate the clinical outcome of autogenous dermis combined with local flap transplantation in the treatment of titanium mesh exposure after cranioplasty. Methods: We studied a total of 8 patients with titanium mesh exposure after cranioplasty. After debridement of the head wound, the autogenous dermal tissue from the lateral thigh was transplanted to the surface of titanium mesh, and the local skin flap was then applied after suturing and fixation to repair the wound on the surface of the dermis. To repair the lateral thigh dermal tissue area, a local skin flap was obtained, and a blade thick skin graft was used. Results: Both dermal tissue and local skin flap survived. In the meanwhile, the donor skin area of the lateral thigh healed well, with only slight scar hyperplasia, and the titanium mesh was preserved. There was no recurrence after 6 months of follow-up. Conclusions: The application of autogenous dermis combined with local skin flap to repair titanium mesh exposure can effectively avoid skin flap necrosis, potential re-exposure of titanium mesh, sub-flap effusion, infection, and other problems. This method has an ideal effect, has easy access to materials, and reduces patients' economic burden. It is worth popularizing.